Air index compensated interferometer as a prospective novel primary standard for baseline calibrations. (1st July 2015) - Meiners-Hagen, Karl; Bošnjakovic, Alen; Köchert, Paul; Pollinger, Florian
Abstract: We describe the status of the development of an interferometer for absolute distance measurements with an intrinsic compensation of the refractive index of air, intended as a primary standard for the calibration of geodetic baselines. Two frequency-doubled Nd:YAG lasers are offset locked with a frequency difference of ≈20 GHz at the infrared 1064 nm fundamental wavelength. The resulting synthetic wavelengths of 15 mm for the infrared and 7.5 mm for the frequency-doubled green light are used as the scale for the measurements. Longer synthetic wavelengths are generated by acousto-optic frequency shifters. Based on the dispersion in air between green and infrared light the refractive index can be compensated. The attempt is demanding since uncertainties of the interferometric measurements for the optical wavelengths are scaled by a factor of nearly 300 000 in the refractive index compensated result. First comparisons up to 50 m length between this interferometer and a HeNe reference are presented. The deviations are smaller than ± 200 µ m and dominated by a non-linearity from problems in the collimation of the measurement beams. In the linear parts the deviations are below ± 100 µ m.